Empathy and its limits - Assmann, Aleida; Detmers, Ines (Palgrave Macmillan, 2016)
This volume extends the theoretical scope of the important concept of empathy by analysing not only the cultural contexts that foster the generating of empathy, but in focusing also on the limits of pro-social feelings and the mechanisms that lead to its blocking
Keywords: Einfühlung